In service inspections of thick walled concrete sructures - Pecinka, L.; Moravka, S. (Проблемы прочности, 2006)
Ageing management and renewal of the operating license of existing NPP’s are at present the main problems of nuclear power industry. For the ageing management of concrete structures the OECD-Nuclear Energy Agency, Committee on the Safety on Nuclear Installations defined as the first priority ISI techniques for reinforced concrete structures having thick sections and areas not directly accessible for inspections. We discuss the NRI Rez research and development program in this field, as well as results, which will be used for qualification of the ISI techniques. Основними проблемами ядерної енергетики є контроль за процесом старіння і відновлення операційних ліцензій існуючих атомних станцій. В якості найбільш пріоритетного направлення контролю за процесом старіння бетонних конструкцій використовуються так зван ISI-методи для залізобетонних товстостінних онструкцій,що мають недоступні для огляду місця.Обговорюється науково-дослідна програма в цій області,а також деякі результати, що використовуються в кваліфікаційному аналізі ISI-методів. Основными проблемами ядерной энергетики являются контроль процесса старения и возобновление операционных лицензий существующих атомных станций. В качестве наиболее приоритетного направления контроля процесса старения бетонных конструкций используются так называемые lSl-методы для железобетонных толстостенных конструкций с недоступными для осмотра участками. Обсуждается научно-исследовательская программа в этой области, а также некоторые результаты, используемые в квалификационном анализе lSl-методов.